2011
DOI: 10.1080/00224540903365372
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Motives and Sexual Conservatism as Predictors of Sexual Behaviors

Abstract: This study was designed to provide an assessment of the relationship between the two most important implicit motives and the most frequently studied sexual behaviors. A community sample of 102 men and 92 women completed measures of implicit power and affiliation-intimacy motives, sexual conservatism, social desirability, and sexual behavior. For men, high power motivation was positively associated with the number of sexual partners and the frequency of sex. There was an interaction between sexual conservatism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It is theoretically expected that these additional factors contribute to the prediction of behavior, both as main effects and in interaction with motives and motivation (McClelland, 1987;Schultheiss, Kordik, Kullmann, Rawolle, & Rösch, 2009). Nonetheless, various previous studies operated under the assumption that, averaged across situations, higher motives and/or higher motivation lead as a main effect to more instrumental behavior (e.g., McAdams et al, 1984a;Schultheiss, Dargel, & Rohde, 2003;Zurbriggen, 2011;Zygar et al, 2018a). In the current analyses, we also take this stance and focus on the marginal main effects of motivational variables on everyday behavior.…”
Section: The Influence Of Motive Dispositions and Motivational Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is theoretically expected that these additional factors contribute to the prediction of behavior, both as main effects and in interaction with motives and motivation (McClelland, 1987;Schultheiss, Kordik, Kullmann, Rawolle, & Rösch, 2009). Nonetheless, various previous studies operated under the assumption that, averaged across situations, higher motives and/or higher motivation lead as a main effect to more instrumental behavior (e.g., McAdams et al, 1984a;Schultheiss, Dargel, & Rohde, 2003;Zurbriggen, 2011;Zygar et al, 2018a). In the current analyses, we also take this stance and focus on the marginal main effects of motivational variables on everyday behavior.…”
Section: The Influence Of Motive Dispositions and Motivational Statesmentioning
confidence: 99%
“…So far, research has mainly focused on the relations between dispositional agency motives and relationship behavior, for example, the implicit power motive predicting agentic leadership and persuasive behaviors in friendships (McAdams et al, 1984a; see also Ackerman & Corretti, 2015;Mason & Blankenship, 1987;Zurbriggen, 2000Zurbriggen, , 2011. Further, dispositional implicit and explicit independence motives were associated with couples' living arrangements, that is, whether men or women at different ages were coresident with their partner or living apart (Hagemeyer, Schönbrodt, Neyer, Neberich, & Asendorpf, 2015).…”
Section: Two Implementation Styles Of the Agency Motivementioning
confidence: 99%
“…Implicit attitudinal measures have also been used to examine the extent to which sexual motivation unfolds in theoretically predictable ways (without necessitating individual conscious behavioral choice). For example, as discussed earlier regarding studies using self-report measures to show strong gender differences in power motives predicting profligate sexuality, research has shown that men primed with implicit power motives (using imaginative, fictional writing) display effects paralleling findings with explicit measures (Zurbriggen, 2000), whereas implicitly measuring power motives and sexual conservatism revealed that only women low in sexual conservatism display profligate sexuality when power motive is high (Zurbriggen, 2011). Thus, although research using implicit attitudinal measures is still in its infancy, the literature on attitude theory and methodological challenges and successes is highly informative regarding interrelations among sexuality and culture.…”
Section: Personalitymentioning
confidence: 83%
“…Because of the asymmetrical power relations between the genders, men’s sexual objectification does not have a derogating effect, as opposed to women—whose sexual objectification activates their traditional role as sex objects (Kahalon, Shnabel, & Becker, 2018b) and reminds them of their (inferior) place in the gender hierarchy. Moreover, men’s sexuality is associated with dominance and pride (e.g., Rudman, Fetterolf, & Sanchez, 2013; Zurbriggen, 2000, 2011) as opposed to women’s sexuality—which is associated with submission (Kiefer, Sanchez, Kalinka, & Ybarra, 2006; Sanchez, Kiefer, & Ybarra, 2006) and considered a source of shame (e.g., V. Klein, Imhoff, Reininger, & Briken, 2018; Tolman & Tolman, 2009; Welles, 2005).…”
Section: Women’s Sexual Objectification Of Menmentioning
confidence: 99%